2015
DOI: 10.1103/physrevlett.115.056601
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Structure Dependent Spin Mixing Conductance in Cobalt Thin Films

Abstract: Reprinted with permission from the American Physical Society: Physical Review Letters 115, 056601 c (2015) by the American Physical Society. Readers may view, browse, and/or download material for temporary copying purposes only, provided these uses are for noncommercial personal purposes. Except as provided by law, this material may not be further reproduced, distributed, transmitted, modi ed, adapted, performed, displayed, published, or sold in whole or part, without prior written permission from the American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 29 publications
9
42
0
Order By: Relevance
“…The dependence on Cu thickness was not studied previously, however it is a reasonable assumption based upon other studies of Co/Ru/Co that upon increasing the Cu thickness further, I c R N would also have increased in that system [53]. We attributed the observations of our previous work to the fcc interlayers modifying the growth morphology of the Co layers from a mixed fcc/hcp growth without the fcc interlayers (a known phenomena creating stacking faults in the Co grains [54], which may be responsible for suppressing supercurrent) to pure fcc growth with the fcc interlayers (which caused an increase in supercurrent propagation by removing the stacking faults). The increasing I c R N with interlayer thickness in this work is most likely due to improved growth morphology of the Co/Ni multilayer by the same mechanism.…”
Section: Discussionmentioning
confidence: 57%
“…The dependence on Cu thickness was not studied previously, however it is a reasonable assumption based upon other studies of Co/Ru/Co that upon increasing the Cu thickness further, I c R N would also have increased in that system [53]. We attributed the observations of our previous work to the fcc interlayers modifying the growth morphology of the Co layers from a mixed fcc/hcp growth without the fcc interlayers (a known phenomena creating stacking faults in the Co grains [54], which may be responsible for suppressing supercurrent) to pure fcc growth with the fcc interlayers (which caused an increase in supercurrent propagation by removing the stacking faults). The increasing I c R N with interlayer thickness in this work is most likely due to improved growth morphology of the Co/Ni multilayer by the same mechanism.…”
Section: Discussionmentioning
confidence: 57%
“…The mixing conductance of the magnetic insulator yttrium iron garnet (YIG) was predicted to be of the same order of magnitude as that of magnetic metals [4], which was subsequently confirmed by experiments [5,6]. A dependence of the spin mixing conductance on the interface cut and orientation to the normal metal has also been predicted [4] and confirmed [7,8]. This anisotropy could partly be explained by the density of the local Fe magnetic moment directly at the interface.…”
Section: Introductionmentioning
confidence: 74%
“…For instance, Li et al found nearly isotropic absorption of pure spin currents in the Py 1-x Cu x /Cu/Co trilayers, while Baker et al found the anisotropic absorption of pure spin currents for the Co 50 Fe 50 /Cr/Ni 81 Fe 19 spin valves [18,19]. Besides, Tokac et al have corroborated the interfacial structure dependent non-local Gilbert damping in Co/Ir multilayers with fcc(111) or hcp(0001) interfacial textures [20]. However, the dependence of non-local damping on magnetization orientation has attracted continuous attention, but is still disputed [21][22][23][24].…”
Section: Introductionmentioning
confidence: 95%